2023
DOI: 10.3176/tr.2023.1.03
|View full text |Cite
|
Sign up to set email alerts
|

The Buddhist and Christian Perspectives on Business Ethics in Leading Chinese Business Practices

Abstract: The religious practices of ethnic Chinese business leaders make an interesting debate for exploring how leadership, ethics and perspective are seen because of the sharp distinction made between 'before' and 'after'. Business ethics applied to economics and business has a long tradition. While Buddhism focuses on experientially based ethical consciousness to develop the business with self-responsibility, Christian faith and reason intertwine to bring about principles, criteria, and guidelines for action and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Business ethics become individual. In that case, so-called business ethics can be seen as nothing more than a moral movement, which requires public opinion to be effective (Roy et al, 2023;Yew & Tan, 2023) Buddhist teachers from various traditions have demonstrated what is called a Buddhist moral phenomenological approach to ethics, but explicit identification does not emerge until the attainment of Bodhisattva hood. The philosophy of business ethics looks at how ethics centered on enological phenomena plays a role in various Buddhist traditions.…”
Section: Conceptual Of Business Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Business ethics become individual. In that case, so-called business ethics can be seen as nothing more than a moral movement, which requires public opinion to be effective (Roy et al, 2023;Yew & Tan, 2023) Buddhist teachers from various traditions have demonstrated what is called a Buddhist moral phenomenological approach to ethics, but explicit identification does not emerge until the attainment of Bodhisattva hood. The philosophy of business ethics looks at how ethics centered on enological phenomena plays a role in various Buddhist traditions.…”
Section: Conceptual Of Business Ethicsmentioning
confidence: 99%
“…(Simonds, 2021) From this, a person's speech becomes improved, and thus his or her action. Once he or she is working on right action, it becomes natural to incline towards a virtuous livelihood (Harvey, n.d.;Yew & Tan, 2023) Humanistic Buddhism's Approach to Ethics Kammavāda (Pāli ) (Nucci, 2008), recognition that there is a causal correlation. between what we do and what we get as a result; Kiriyavāda (Pāli): awareness of the need to perform morally wholesome actions and refrain from morally unwholesome actions; Viriyavāda (Pāli): recognition and provision of the role of human effort in the pursuit of the moral life.…”
Section: Conceptual Of Business Ethicsmentioning
confidence: 99%